RESPONSE OF GROWTH AND YIELD OF CURLY RED CHILI PLANTS (capsicum annum L.) TO VARIOUS CONCENTRATIONS OF THE GROWTH REGULATOR PACLOBUTRAZOL - Putri, Yohana Enda; Ariefin, Muhammad Noor; Rofita, Dewi (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Curly red chili pepper (Capsicum annum L.) is one of the horticultural commodities with high economic value for development. One effort to increase the production yield of curly red chili plants is by using the growth regulator Paclobutrazol. Paclobutrazol is a growth regulator that can inhibit vegetative growth and stimulate generative growth in plants, such as flower formation and fruit development. The aim of this research was to determine the response and the appropriate concentration of the growth regulator Paclobutrazol on the growth and yield of curly red chili (Capsicum annum L.). This study was conducted in Bangka Leda Village, Langke Rembong District, Manggarai Regency, for 5 months, from April 2024 to August 2024. The study used a randomized block design consisting of one factor, namely Paclobutrazol concentration, with 6 treatment levels. The treatments used were P0 = No Paclobutrazol, P1 = Paclobutrazol concentration of 200 ppm/liter of water, P2 = Paclobutrazol concentration of 300 ppm/liter of water, P3 = Paclobutrazol concentration of 400 ppm/liter of water, P4 = Paclobutrazol concentration of 500 ppm/liter of water, and P5 = Paclobutrazol concentration of 600 ppm/liter of water. The observational data obtained in this study were analyzed using Analysis of Variance (ANOVA). If the results showed significant effects, they would be followed by an Honest Significant Difference (HSD) test at a 5% level. The results of the study indicated that the application of various concentrations of Paclobutrazol growth regulator had significant effects on parameters such as plant height (inhibiting plant height), number of branches (inhibiting the number of branches), flowering time, harvest time, number of fruits, and fresh fruit weight of curly red chili plants. The application of Paclobutrazol growth regulator at a concentration of 600 ppm/liter of water (P5) was able to inhibit plant height and the number of branches, while providing optimum results for generative growth, such as 50% flowering time (days), harvest time (days), number of fruits (pieces), and fresh fruit weight (g) of curly red chili plants.